LINGUOCULTURAL AND LINGUISTIC TRANSLATION ASPECTS OF SOCIOPOLITICAL TERMS AND THEIR TRANSLATION FROM ENGLISH INTO THE KARAKALPAK LANGUAGE DURING THE PERIOD OF GLOBALIZATION - Najimova Perizad Arslanbay qizi (Social science and innovation, 2024)
This article investigated the importance of political terminology in linguistics as well as providing feedback on the subject. This article discusses the theoretical nature of the use of socio-political terms in English and Karakalpak languages. Also in linguistics, information about the use of terms is described.